Pengelompokkan Sembilan Kabupaten/Kota di Provinsi Sumatera Barat Berdasarkan Tingkat Kriminalitas dengan Menggunakan Analisis Gerombol - Chairina Wirdiastuti; Helma Helma (Journal of Mathematics UNP, 2019)
Abstract Crime is an act that violates the law. Sumatra Barat Province have a high criminal. Criminals can make big problem for criminal victims, such as death, disability, material losses and others. The increase of crime is caused by several problem such as economic, social, conflict and etc. Crime is an element that explains the quality of sociaty and the law of a region. For that, it is necessary to know the groups of regencies/cities in the Province of Sumatera Barat based on crime rates so that the government can evaluate crime and improve some policies towards a region that has high crime. Data was obtained from the Central Agency on Statistics which showed the number of cases that occurred in regencies/cities in Sumatra Barat Province. Using cluster analysis with hirarchical method, it was concluded that regencies/cities in Sumatra  Barat province were divided into three groups where group one consist of Solok Regency, group two consist of Tanah Datar Regency, Padang Pariaman Regency, Lima Puluh Kota Regency, Solok Selatan Regency, Dharmasraya Regency, Pariaman City, and Sawahlunto City and group three consists of Bukittingi City.KeywordsCrime, Cluster Analysis,  Hierarchical Method